Holistic Pedadogy of Family-Based for Adolescent Identity Development - Hidayat, Ade; Nurhayati, Tati (Indonesian Journal of Educational Counseling, 2022)
Adolescent’s deviate behavior may be caused by many different factors. A symptom of deviation that arose is just an indicator of a bigger crucial problem inside. Complexity of affective, cognitive and psychomotor in adolescence period that did not obtain proper nurture and guidance could bring them to an anomaly way. State of full guidance on adolescent brings them to finished development period and creates holistic awareness about their true identity as an entity of huge universe civilization. Holistic pedagogy comes to bring a discourse as thinking basic for describing about how to humanize adolescent that starts from the first step, home. The importance of human awareness as an entity of universe civilization with its tasks is a duty of adolescent’s development that often disappear from chains of multigenerational transmission in family, school and societal environment, where it is considered as a trigger of nowadays adolescent problems.